How to influence the customer journey: the role of information on mobile food ordering applications - Conde, Beatriz Jóia Serrasqueiro de Sousa (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Marketing Research and CRM